Competition between barnyardgrass and soybean cultivated in hydromorphic soil. II. Effect on some agronomic characteristics - Saccol, Ailo Valmir; Estefanel, Valduino (Pesquisa Agropecuaria Brasileira, 1995)
The objective was to study the interaction between duration of competition of barnyardgrass (Echinocloa spp.) and row spacing on some agronomic characteristics of soybean grown in a hydromorphic soil. The results indicated that as the competition period increased there was a reduction in plant height and insertion of the lower pods, stem diameter and leaf area index. However, the reduction rate was affected by row spacing and weed population. The narrow row spaces, by decreasing intraspecific competition, resulted in higher plants and greater leaf area index. The duration of competition after which there was a significant effect on plant height was 20 days for the 40 em rows and 30 days for the 60 cm and 80 cm rows, whereas for leaf area index this period was 22 days. Among the agronomic characteristics studied, the one that was most related to seed yield was stem diameter.